Beyond Knowledge Transmission: Pedagogy and Ideological Formation in Indonesian Reformist Pesantren - Muhajir Abd. Rahman; La Adu; La Jusu; La Rajab; La Sugi; Elfridawati Mai Dhuhani (Jurnal Pendidikan Islam, 2026)
Islamic education is increasingly recognized worldwide not merely as a method of transmitting religious knowledge but also as a vital space where ideology, moral authority, and religious subjectivities are actively shaped. In light of modernization and institutional reforms, exploring how pedagogical approaches influence religious identity has emerged as a pivotal concern in contemporary Islamic education scholarship. This study analyzes how Persatuan Islam (Persis) pesantren functions as an ideological–pedagogical system that reproduces a reformist Islamic orientation through the integration of ta’līm, tarbiyah, and ta’dīb. Employing a qualitative case study design, data were collected through semi-structured interviews with teachers, administrators, and students, participant observation of classroom and dormitory life, and analysis of institutional documents. The findings reveal that pedagogy in Persis pesantren operates as a holistic and continuous process embedded in daily routines, disciplinary structures, and scriptural instruction. Through structured knowledge transmission, embodied moral training, and ethical regulation, students internalize doctrinal authority and develop a durable religious habitus that extends beyond institutional boundaries. The study concludes that pedagogy functions as a central mechanism of ideological reproduction and religious subject formation. These findings imply the need to conceptualize Islamic education as a practice-oriented and value-embedded process, offering a theoretical framework for understanding pesantren pedagogy within contemporary Indonesian and global Islamic educational contexts.